DAMPAK PERKEMBANGAN IKLAN MAKANAN RINGAN BAGI ANAK-ANAK - Ana Rosmiati (Gelar : Jurnal Seni Budaya, 2012)
Childhood  is the most vulnerable time to try something new  especially food and drink. Children are easily interested in snacks advertized in television. They do not know how dangerous it is to health if manufacturers do not pay a close attention to the composition of the snack. It is their parents who should monitor the child’s behavior in consuming the snack. This paper aims to find out the impact of advertisement  on snacks to children’s health.  The data was collected through literary study such as books, journals and so on. An advertisement is very influential to children’s behavior in choosing their snack. Children do not know the danger of consuming the snack. Parents should monitor the snack bought by children. Key words : children, snack, advertisement, television